Peningkatan Motivasi belajar IPA Menggunakan Pendekatan Saintifik pada siswa kelas IV SD IT AN-NUR - Farah Zhafiroh Nuradi (Prosiding University Research Colloquium, 2021)
This study aims to increase motivation and science learning outcomes by applying ascientific model with the research subjects of fourth grade students at SD IT AN-NUR,Sawangan District, Magelang Regency. The research method used is CAR (classroomaction research). The procedure in this study consisted of four stages, namely theplanning stage, the implementation stage, the observation stage and the reflectionstage. Data were taken through observation techniques, and questionnaires. The datawere analyzed by means of descriptive qualitative and descriptive quantitative. In thefirst cycle got an average of 65.71. In the second cycle get an average of 79.04. Based onthis, it can be concluded that the scientific model can increase learning motivation, thusthe scientific model can be used as an alternative to problems regarding learningmotivation.